2016
DOI: 10.1186/s13052-016-0252-9
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus-associated hospitalization in premature infants who did not receive palivizumab prophylaxis in Italy: a retrospective analysis from the Osservatorio Study

Abstract: BackgroundDue to different social and epidemiological factors, the eligibility criteria to receive palivizumab prophylaxis may be different between countries, especially in “otherwise healthy” late preterm infants.MethodsWe analyzed an Italian database of young children referred to emergency departments for acute lower respiratory tract infection (ALRI) during the RSV season over a four year period, when the use of palivizumab as prophylaxis for RSV disease was not widespread in premature infants. The demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This result confirms the literature data that highlights aggressiveness of RSV in premature infants. [2, 28, 30, 33]. In 2017, a large retrospective work on prematures [13] identified an oxygen supplementation rate of around 80% and a PICU admission rate of 22%, while in our work emerged a lower rate both for O2 supplementation (62%) and PICU admission (16,1%), but a raising trend for both parameters.…”
Section: Discussionmentioning
confidence: 42%
“…This result confirms the literature data that highlights aggressiveness of RSV in premature infants. [2, 28, 30, 33]. In 2017, a large retrospective work on prematures [13] identified an oxygen supplementation rate of around 80% and a PICU admission rate of 22%, while in our work emerged a lower rate both for O2 supplementation (62%) and PICU admission (16,1%), but a raising trend for both parameters.…”
Section: Discussionmentioning
confidence: 42%
“…After 18 months of age, however, RSVH was rare [59]. A recent retrospective analysis from the Osservatorio Study in Italy [60], which enrolled three different gestational age group infants (<29, 29 to <32 and 32–35 wGA), found that the percentage of hospitalized preterm infants ≤12 months old that were RSV positive progressively decreased from 40.0% to 28.6% and 18.4% with increasing wGA ( P  = 0.43). These data suggest that, at least in the first year of life, the most premature infants were more vulnerable and prone to RSV infection [60].…”
Section: Resultsmentioning
confidence: 99%
“…However, following the most recent modification by the American Academy of Pediatrics based on American studies on RSV epidemiology [ 4 ], in September 2016, the Italian Drug Agency (AIFA) decided the total financial coverage of the palivizumab prescription to the healthy preterms by the National Health Service, should be limited to the < 29 wGA group and age ≤ 12 months at the beginning of the RSV epidemic season (RES) [ 5 ]. However, the vulnerability of otherwise healthy premature infants, and most notably in the < 32 wGA category was demonstrated by an Italian retrospective analysis on RSV-associated hospitalization during the RSV epidemic season, over a 4 year period, when the use of prophylaxis palivizumab was not widespread in premature infants [ 6 ]. Moreover, a recent study on total costs for hospitalizations and emergency room and/or outpatient visits in infants in the first 3 years of life in Lombardy (Italy) showed that extending palivizumab prophylaxis to 29–32 wGA infants appeared to be a cost-effective strategy [ 7 ].…”
Section: Dear Editormentioning
confidence: 99%